An Overview and Analysis of the Impacts of Extreme Heat on the Aviation Industry - Brandon T Carpenter (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
Weather is a common cause of flight delays and cancellations. However, the vast majority of the time when thinking about weather and its effect on aviation, winter conditions such as snow come to mind. Heat is usually one of the last types of weather we associate with airline challenges. Recently, a bomb cyclone made headlines for the disruptions it caused with travel, especially at John F. Kennedy International Airport. Interestingly, the exact opposite of winter weather conditions can cause just as many challenges. During the summer of 2017, a number of flights at various airports such as Phoenix Sky Harbor International were cancelled because the temperature on the runways was physically too hot for the planes to take off. The cancellations themselves only affected smaller, regional aircraft, but high temperatures still significantly affect larger Boeing and Airbus aircraft in the form of weight restrictions that often result in less passengers, less cargo, and potential delays in departure. This research overviews and analyzes the incident that occurred in Phoenix and details how heat significantly affects both small and large aircraft. The study poses several potential solutions including increasing runway lengths, adjusting airport routing, swapping aircraft, adjusting departure times, improving aircraft design, and decreasing on-board weight that can help mitigate the negative effects of extreme heat on the aviation industry.
Keywords: aviation; heat; airlines; aerospace; weight restriction; flight delays